(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The low level of scientific literacy among elementary school students highlights the need for innovative digital learning media. This condition is influenced by learning activities dominated by lecture methods and limited use of technology-based media, causing students to be less active in understanding scientific concepts. This Research and Development (R&D) study using the 4D model aimed to develop Scratch-based interactive multimedia that is valid, practical, and effective to improve scientific literacy on the topic of Changes in States of Matter in fourth-grade Science and Social Studies (IPAS). The study was conducted at SD Muhammadiyah 1 Sugio involving 48 fourth-grade students, consisting of 24 students in the experimental class and 24 students in the control class. Data were collected through validation sheets, student response questionnaires, student activity observation sheets, and scientific literacy tests (pretest and posttest). Validation results indicated that the multimedia was highly valid, with scores of 3.88 from the media expert, 3.89 from the material expert, 3.97 from the design expert, and 3.85 from the learning instrument validator. The N-Gain Score analysis showed the experimental class achieved 73.99% improvement, while the control class reached 60.25%. Therefore, Scratch-based interactive multimedia is valid, practical, and effective for improving students’ scientific literacy